2022
DOI: 10.1007/s10578-022-01393-w
|View full text |Cite
|
Sign up to set email alerts
|

The Tutor of Resilience Program with Children Who Have Experienced Maltreatment: Mothers’ Involvement Matters

Abstract: Resilience is a dynamic process involving the presence and interaction of personal and environmental factors that modify the impact of adversity. Resilience-building interventions are therefore important for improving trauma-related outcomes in children and caregivers exposed to adversity. This study examines the impact of the Tutor of Resilience (TOR) program on beneficiaries’ trauma-related symptoms and on mother–child interactions in a group of children exposed to maltreatment (N = 186; mean age = 11.95; SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Previous studies conducted in war settings have shown that recovery, sustainability and growth are highly dependent on the protective resources available to the community and the strengths that are nurtured before and during the negative event ( Zautra et al, 2010 ; Ungar, 2011 ). Based on this assumption, the current study examined protective processes described by Ukrainian youth undergoing training in the Tutor of Resilience Program (ToR; Giordano et al, 2021 , 2022 ) to promote resilience with peers in their communities during the early months of the war. The ToR Program offers a model of building resilience during emergencies that is flexible to meet the contextual, cultural, and individual needs of participants and communities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in war settings have shown that recovery, sustainability and growth are highly dependent on the protective resources available to the community and the strengths that are nurtured before and during the negative event ( Zautra et al, 2010 ; Ungar, 2011 ). Based on this assumption, the current study examined protective processes described by Ukrainian youth undergoing training in the Tutor of Resilience Program (ToR; Giordano et al, 2021 , 2022 ) to promote resilience with peers in their communities during the early months of the war. The ToR Program offers a model of building resilience during emergencies that is flexible to meet the contextual, cultural, and individual needs of participants and communities.…”
Section: Introductionmentioning
confidence: 99%